Mechanofluorochromism of NIR-emitting dyes based on difluoroboron β-carbonyl cyclic ketonate complexes. (September 2018) - Zhang, Fushuang; Zhai, Lu; Feng, Siwei; Mi, Wenhua; Sun, Jingbo; Sun, Meng; Zhao, Jinyu; Lu, Ran
Abstract: New difluoroboron β-carbonyl cyclic ketonate complexesCnB (n = 2, 16), in which carbazole was linked to difluoroboron β-diketonate directly, andDCnB (n = 2, 16), where two terminal carbazole units were bridged by vinyl groups to link to difluoroboron β-diketonate core, were synthesized. They exhibited reversible mechanofluorochromic (MFC) behavior under grinding/fuming or heating treatment. Particularly, the emission ofDC2B andDC16B emerged in the range of 650–850 nm in the solid-state. They gave red and rose-red luminescence in the as-synthesized crystals and in the ground powders, respectively, during MFC processes. Such MFC materials emitting NIR (near-infrared) light were seldom reported. In addition, compared withC2B, C16B showed high-contrast mechanofluorochromism because the long alkyl chain might decrease the strength of π-π interactions in the as-synthesized crystals, leading to the emission appeared at the high-energy region (483 nm). The disassembling of parts of π-aggregates and the improvement of the molecular planarity led to red-shift of the emission (509 nm) upon grinding. Graphical abstract: Highlights: New difluoroboron β-carbonyl cyclic ketonate complexes bearing N- alkylcarbazole were synthesized. The synthesized difluoroboron β-diketonate complexes showed reversible mechanofluorochromism. NIR dyes emitted red and rose red light during mechanofluorochromic processes. DyeC16B showed high-contrast mechanofluorochromism compared with dyeC2B .